A Systematic Review with Thematic Synthesis of the Experience of Hospitalization in People with Advanced Chronic Obstructive Pulmonary Disease. (3rd September 2021) - Bakthavatsalu, Barathi; Walshe, Catherine; Simpson, Jane
Abstract: Hospital admissions are common for people with advanced chronic obstructive pulmonary disease (COPD). To provide effective, responsive care, it is important to understand how people experience hospitalization. The aim of this review was to explore the experience of hospitalization in people with advanced COPD, drawing from qualitative research data. Guided by a thematic synthesis approach, a systematic search of databases ( n = 13) including PubMed, CINAHL, PsycINFO and ProQuest was undertaken from database inception to May 2020. Inclusion criteria included papers reporting qualitative research focused on any aspect of hospitalization for people with advanced COPD and reported in English language from peer reviewed journals. Following quality appraisal, relevant data were extracted, and a three-stage thematic synthesis method used to develop inductive themes. From 1935 papers, the 11 included studies focused on specific aspects of hospitalization (e.g., care and treatment), rather than the totality of the experience. Four analytical themes were identified: unpredictable hospitalization, benefits and burdens of treatment, overwhelming distress and the communicative attitude of staff. Hospitalization was unpredictable because of the frequent, sudden admissions required for acute breathlessness. Hospital could be perceived both as a safe place, due to immediate symptom relief, but also as a place for experiencing overwhelming distress. Breathlessness was the most difficult symptom experienced, causing physical and psychological distress. Both communication and attitudes of the staff could influence the experience. A holistic approach to the care of hospitalized individuals with advanced COPD is required to improve care. Supplemental data for this article is available online at https://doi.org/10.1080/15412555.2021.1971186 .